The Impact of Using Artificial Intelligence on the Accounting and Auditing Profession in Light of the Corona Pandemic - Rashwan, Abdul Rahman M. S.; Alhelou, Eitedal M. S. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2020)
The study aims to identify the impact of the use of artificial intelligence on the accounting and auditing profession in light of the Corona pandemic. The descriptive and analytical approach was used to define the problem of the study and define the theoretical framework for the study. The statistical program (SPSS) was also used to answer research questions and test hypotheses. The two researchers used the questionnaire as a tool for the field study, as it was distributed to the study sample consisting of accountants and auditors from the owners of accounting and auditing offices in Gaza Strip, their number (170) questionnaires, and (155) questionnaires were retrieved. The results of the study concluded that there is a significant impact of the use of artificial intelligence on improving and developing the quality of professional performance of accountants and auditors, increasing the ability to complete complex accounting and auditing work, improving and developing the efficiency of accounting and auditing cadres, and developing accounting and auditing systems in light of the Corona pandemic. The study recommended the necessity for accounting and auditing offices in Gaza Strip to use artificial intelligence for the great cycle that it will undertake in improving the efficiency of the accounting and auditing process by providing the required results in a timely manner, especially in light of the Corona pandemic.